Sensitivity of feedback effects in CBMZ/MOSAIC chemical mechanism. (August 2015) - San José, R.; Pérez, J.L.; Balzarini, A.; Baró, R.; Curci, G.; Forkel, R.; Galmarini, S.; Grell, G.; Hirtl, M.; Honzak, L.; Im, U.; Jiménez-Guerrero, P.; et al.
Abstract: To investigate the impact of the aerosol effects on meteorological variables and pollutant concentrations two simulations with the WRF-Chem model have been performed over Europe for year 2010. We have performed a baseline simulation without any feedback effects and a second simulation including the direct as well as the indirect aerosol effect. The paper describes the full configuration of the model, the simulation design, special impacts and evaluation. Although low aerosol particle concentrations are detected, the inclusion of the feedback effects results in an increase of solar radiation at the surface over cloudy areas (North-West, including the Atlantic) and decrease over more sunny locations (South-East). Aerosol effects produce an increase of the water vapor and decrease the planet boundary layer height over the whole domain except in the Sahara area, where the maximum particle concentrations are detected. Significant ozone concentrations are found over the Mediterranean area. Simulated feedback effects between aerosol concentrations and meteorological variables and on pollutant distributions strongly depend on the aerosol concentrations and the clouds. Further investigations are necessary with higher aerosol particle concentrations. WRF-Chem variables are evaluated using available hourly observations in terms of performance statistics. Standardized observations from the ENSEMBLE system web-interface were used. The research was developed under the second phase of Air Quality Model Evaluation International Initiative (AQMEII). WRF-Chem demonstrates its capability in capturing temporal and spatial variations of the major meteorological variables and pollutants, except the wind speed over complex terrain. The wind speed bias may affect the accuracy in the chemical predictions (NO2, SO2 ). The analysis of the correlations between simulated data sets and observational data sets indicates that the simulation with aerosol effects performs slightly better. These results indicate potential importance of the aerosol feedback effects and an urgent need to further improve the representations in current atmospheric models to reduce uncertainties at all scales. Highlights: Aerosol feedbacks effects were examined during one year simulation with WRF-Chem model and CBMZ-MOSAIC chemical mechanism. Higher solar radiation and lower near surface temperatures are observed over North Atlantic Ocean with indirect effects. Indirect feedback effects make to increase non convective rain and water vapor. Cloud droplet numbers are much lower when WRF-Chem uses aerosol concentrations than WRF default value. Performance is similar for both simulations but sensitivity of the meteorology and pollution to the aerosols is important.